2020
DOI: 10.1038/s41380-020-0707-7
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR disruption and UK Biobank analysis of a highly conserved polymorphic enhancer suggests a role in male anxiety and ethanol intake

Abstract: A 2020, 'CRISPR disruption and UK Biobank analysis of a highly conserved polymorphic enhancer suggests a role in male anxiety and ethanol intake', Molecular Psychiatry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 48 publications
(68 reference statements)
3
25
0
Order By: Relevance
“…We have previously shown that the GAL5.1 enhancer controls anxiety and alcohol intake [ 24 ]. This provided us with a unique opportunity to determine the effects of environmental factors such as dietary changes and early life stress on 5mC/5hmC levels within an enhancer region shown to control behaviours with a direct effect on human health.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that the GAL5.1 enhancer controls anxiety and alcohol intake [ 24 ]. This provided us with a unique opportunity to determine the effects of environmental factors such as dietary changes and early life stress on 5mC/5hmC levels within an enhancer region shown to control behaviours with a direct effect on human health.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to examining the effects of environmental factors on levels of 5mC/5hmC within GAL5.1 we also explored the effects of DNA methylation on the activity of GAL5.1 as well as its response to known stimuli such as PKC stimulation and expression of EGR1 [ 23 , 24 ]. To address this question, we first cloned the human GAL5.1 (GG) enhancer into the pCpGfree-promoter-Lucia luciferase vector that lacks CpG dinucleotides and contains the EF-1α promoter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations